Pemikiran Al-Farabi dan Ibnu Sina - Santalia, Indo; N, Nurhaerat (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research was carried out by studying and reading books related to Islamic thought figures, namely Al-Farabi and Ibnu Sina. The presence of these two great Islamic figures was able to have a positive impact on the development of Islamic thought, and opened up the horizons of thinking, so that they were able to become role models for Muslim philosophers to follow after them. It is from his works that the world is enlightened, both in the field of medicine and in other fields, such as emanation, soul and prophecy. Al-Farabi and Ibnu Sina themselves became the spearheads for the Islamic generation after Al-Kindi. It was from them that the Islamic generation learned a lot about Islamic philosophy, although there is still much debate between Islamic scholars and generations about their thoughts. However, in essence, they have made the best contribution through their scientific works.